2012
DOI: 10.1590/s1413-78522012000300007
|View full text |Cite
|
Sign up to set email alerts
|

Fraturas do colo do talus: avaliação da reprodutibilidade da classificação de Hawkins

Abstract: ObjectiveTo evaluate the intraobserver and interobserver reproducibility of Hawkins' classification for fractures of the neck of the talus.Methods20 random cases of fracture of the talus were selected, to be defined according to the classification of types by eight orthopedic surgeons, 13 orthopedic residents and 15 radiology residents.ResultsUsing the statistical test of Landis and Koch, measurements of 0.627 and 0.668 were obtained in the first and second evaluations, respectively. These values define a sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…First, the Hawkins classification [4] modified by Canale and Kelly [6] is the most common classification system for talar neck fractures [69,70]. Drummond Filho et al showed that the inter-and intra-rater reliability of the Hawkins classification was generally satisfactory [71]. However, no reliability studies are currently available for the other classifications considered in the included studies.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…First, the Hawkins classification [4] modified by Canale and Kelly [6] is the most common classification system for talar neck fractures [69,70]. Drummond Filho et al showed that the inter-and intra-rater reliability of the Hawkins classification was generally satisfactory [71]. However, no reliability studies are currently available for the other classifications considered in the included studies.…”
Section: Strengths and Limitationsmentioning
confidence: 99%